UMIc: A Preprocessing Method for UMI Deduplication and Reads Correction - Tsagiopoulou, Maria; Maniou, Maria Christina; Pechlivanis, Nikolaos; Togkousidis, Anastasis; Kotrová, Michaela; Hutzenlaub, Tobias; Kappas, Ilias; Chatzidimitriou, Anastasia; Psomopoulos, Fotis (Frontiers in Genetics, 2021)
A recent refinement in high-throughput sequencing involves the incorporation of Unique Molecular Identifiers (UMIs), which are random oligonucleotide barcodes, on the library preparation steps. A UMI adds a unique identity to different DNA/RNA input molecules through PCR amplification, thus reducing bias of this step. Here, we propose an alignment free framework serving as a pre-processing step of FASTQ files, called UMIc, for deduplication and correction of reads building consensus sequences from each UMI. Our approach takes into account the frequency and the Phred quality of nucleotides and the distances between the UMIs and the actual sequences. We have tested the tool using different scenarios of UMI-tagged library data, having in mind the aspect of a wide application. UMIc is an open-source tool implemented in R and is freely available from https://github.com/BiodataAnalysisGroup/UMIc.